COVID‐19 epidemic and mitigation policies: Positive and normative analyses in a neoclassical growth model. (21st October 2021) - Gori, Luca; Manfredi, Piero; Marsiglio, Simone; Sodini, Mauro
Abstract: The COVID‐19 pandemic is still ravaging the planet, but its (short‐, medium‐, and long‐term) diverse effects on health, economy, and society are far from being understood. This article investigates the potential impact of a deadly epidemic and its main nonpharmaceutical control interventions (social distancing vs. testing–tracing–isolation, TTI) on capital accumulation and economic development at different time scales. This is done by integrating an epidemiological susceptible–infectious–recovered model with a Solow‐type growth model including public expenditure, as a parsimonious setting to offer insights on the trade‐off between protecting human lives and the economy and society. The work clarifies (i) the long‐term interactions amongst a deadly infection, demography, and capital accumulation, (ii) the lack of viability of persistent social distancing measures also using an analytical characterization, and the threat of policy‐enhanced COVID‐19 endemicity, (iii) the potentially high return on investments in TTI activities to avoid future lockdowns and related capital disruption. It also quantifies the welfare effects of a range of policies, confirming a counterintuitive role for tax‐funded preventive investments aimed at strengthening TTI as more desirable interventions than generalized lockdowns.